A meta-analysis of genome-wide gene expression differences identifies promising targets for type 2 diabetes mellitus - Tao Huang; Tao Huang; Bisma Nazir; Reem Altaf; Bolun Zang; Hajra Zafar; Ana Cláudia Paiva-Santos; Ana Cláudia Paiva-Santos; Nabeela Niaz; Muhammad Imran; Yongtao Duan; Muhammad Abbas; et al. (Frontiers in Endocrinology, 2022)
Aims/introductionDue to the heterogeneous nature of type 2 diabetes mellitus and its complex effects on hemodynamics, there is a need to identify new candidate markers which are involved in the development of type 2 diabetes mellitus (DM) and can serve as potential targets. As the global diabetes prevalence in 2019 was estimated as 9.3% (463 million people), rising to 10.2% (578 million) by 2030 and 10.9% (700 million) by 2045, the need to limit this rapid prevalence is of concern. The study aims to identify the possible biomarkers of type 2 diabetes mellitus with the help of the system biology approach using R programming.Materials and methodsSeveral target proteins that were found to be associated with the source genes were further curated for their role in type 2 diabetes mellitus. The differential expression analysis provided 50 differentially expressed genes by pairwise comparison between the biologically comparable groups out of which eight differentially expressed genes were short-listed. These DEGs were as follows: MCL1, PTX3, CYP3A4, PTGS1, SSTR2, SERPINA3, TDO2, and GALNT7.ResultsThe cluster analysis showed clear differences between the control and treated groups. The functional relationship of the signature genes showed a protein–protein interaction network with the target protein. Moreover, several transcriptional factors such as DBX2, HOXB7, POU3F4, MSX2, EBF1, and E4F1 showed association with these identified differentially expressed genes.ConclusionsThe study highlighted the important markers for diabetes mellitus that have shown interaction with other proteins having a role in the progression of diabetes mellitus that can serve as new targets in the management of DM.